Psalm 8: human dignity and vulnerability - Snyman, Gerrie (Stellenbosch Theological Journal, 2025)
Psalm 8 contrasts the majesty of the deity with the question about humankind. Despite being proclaimed as a little lower or a little less than divine beings, the contrast itself indicates a level of vulnerability on the side of humankind. If my proposition is true, the question is what kind of vulnerability it is. What is the relationship between being a little lower than a divine being – having dominion over creation – and vulnerability? To answer this question, the psalm is read with the help of various interpretations. Then follows a discussion on vulnerability and the problem of invulnerability. The essay concludes that it is necessary to feel vulnerability and not shut down its feelings. Daily life involves engaging with situations that require openness to vulnerability.